Increased functional sensorimotor network efficiency relates to disability in multiple sclerosis. (August 2021) - Strik, Myrte; Chard, Declan T; Dekker, Iris; Meijer, Kim A; Eijlers, Anand JC; Pardini, Matteo; Uitdehaag, Bernard MJ; Kolbe, Scott C; Geurts, Jeroen JG; Schoonheim, Menno M
Background: Network abnormalities could help explain physical disability in multiple sclerosis (MS), which remains poorly understood. Objective: This study investigates functional network efficiency changes in the sensorimotor system. Methods: We included 222 MS patients, divided into low disability (LD, Expanded Disability Status Scale (EDSS) ⩽3.5, n = 185) and high disability (HD, EDSS ⩾6, n = 37), and 82 healthy controls (HC). Functional connectivity was assessed between 23 sensorimotor regions. Measures of efficiency were computed and compared between groups using general linear models corrected for age and sex. Binary logistic regression models related disability status to local functional network efficiency (LE), brain volumes and demographics. Functional connectivity patterns of regions important for disability were explored. Results: HD patients demonstrated significantly higher LE of the left primary somatosensory cortex (S1) and right pallidum compared to LD and HC, and left premotor cortex compared to HC only. The logistic regression model for disability ( R 2 = 0.38) included age, deep grey matter volume and left S1 LE. S1 functional connectivity was increased with prefrontal and secondary sensory areas in HD patients, compared to LD and HC. Conclusion: Clinical disability in MS associates with functional sensorimotor increases in efficiency and connectivity, centred around S1, independent of structural damage.